2011
DOI: 10.1186/1471-2180-11-267
|View full text |Cite
|
Sign up to set email alerts
|

Reliable identification at the species level of Brucella isolates with MALDI-TOF-MS

Abstract: BackgroundThe genus Brucella contains highly infectious species that are classified as biological threat agents. The timely detection and identification of the microorganism involved is essential for an effective response not only to biological warfare attacks but also to natural outbreaks. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) is a rapid method for the analysis of biological samples. The advantages of this method, compared to conventional techniques, are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 33 publications
2
70
0
8
Order By: Relevance
“…This protocol is considerably faster than previously described protocols, which require several reagents, centrifugation steps, and long incubations (12)(13)(14)(15)(16) or expensive gamma ray sources (17). Sample preparation with the solvent mixture allowed correct MALDI-TOF MS identification of all Brucella strains tested and several other bacterial pathogens.…”
mentioning
confidence: 99%
“…This protocol is considerably faster than previously described protocols, which require several reagents, centrifugation steps, and long incubations (12)(13)(14)(15)(16) or expensive gamma ray sources (17). Sample preparation with the solvent mixture allowed correct MALDI-TOF MS identification of all Brucella strains tested and several other bacterial pathogens.…”
mentioning
confidence: 99%
“…MALDI-TOF MS has been used to identify bacterial species and subspecies (14,15), and in some outbreaks, MALDI-TOF MS has been reported to be able to identify the lineages of strains (16)(17)(18). Recently, MALDI-TOF MS has also been used to detect clinical pathogens previously misidentified or ambiguously identified (19)(20)(21)(22)(23)(24). Detection of antimicrobial resistance using MALDI-TOF MS has been reported for Staphylococcus aureus (25)(26)(27)(28)(29)(30)(31)(32), Acinetobacter baumannii (26), Escherichia coli, and other members of the family Enterobacteriaceae (33)(34)(35).…”
mentioning
confidence: 99%
“…It should be pointed out that because of the high transmissibility of Brucella organisms, an initial bacterial inactivation step with absolute ethanol was added as a measure of caution, to be followed by extraction with formic acid and acetonitrile [69,70]. Although in some studies, the method also enabled discrimination at the species level and even at the biovar level for B. suis [66,67], other investigators reported unreliable discrimination between the different Brucella species [68].…”
Section: Rapid Phenotypic Identification Methodsmentioning
confidence: 99%
“…The method obviates the need for biochemical testing and, thus, is suitable for high-throughput by less skilled laboratory personnel [66,67]. This novel approach can be employed on bacterial colonies growing on agar plates, as well as from positive culture broths and, therefore, it enables direct identification of organisms from blood culture vials [68].…”
Section: Rapid Phenotypic Identification Methodsmentioning
confidence: 99%